P299 CONDUCTION DISORDERS AS THE FIRST HALLMARK OF ISOLATED CARDIAC SARCOIDOSIS IN A HIGHLY ACTIVE INDIVIDUAL: A CASE REPORT. (18th May 2022) - Albani, S; Muccioli, S; Mabritto, B; Scacciatella, P; Musumeci, G
Abstract: A 45–year–old highly active Caucasian individual was admitted to the emergency department complaining of slightly reduced physical performances: he reported a lack of increase of heart rate beyond 80–100 bpm at fitness tracker monitoring during physical activity during the previous week. He used to train 3–4 times/week. He had no previous medical concerns and he didn't take any medication. Basal electrocardiogram (ECG) showed 2:1 atrioventricular block (AVB) and left axis deviation, with the exception of his 2:1 AVB, the other features on the ECG are common training related changes. Transthoracic echocardiogram was normal. Treadmill exercise test revealed paroxysmal 2:1 AVB and Mobitz I AVB at peak effort, then first degree AVB and isolated and coupled right infundibular premature ventricular complexes (PVC) in the recovery phase: exercise related AV–conduction improvement suggested supra–nodal AVB. Cardiac magnetic resonance (CMR) imaging reported two areas of late gadolinium enhancement (LGE) with midwall/subepicardial distribution: the first one in the basal anterior septal wall extending to basal anterior wall and the second one involving the basal and medium segment of inferior septum and inferior wall. LGE quantification was 6.0 g/m2 (9.5%). Short tau inversion recovery (STIR) acquisitions were negative for oedema (Figure 1 ). Subsequent FDG–PET imaging confirmed high uptake in the basal anterior septal wall, the anterior wall and in the basal inferior septal area (Figure 2 ). No other organ involvement was detected. Considering the FDG–PET, LGE and AV–conduction abnormalities, the patient was clinically diagnosed with symptomatic isolated CS. However, a definitive histologic diagnosis was not possible as no myocardial biopsy was performed. High dose corticosteroid therapy was startedand after few days of treatment ECG monitoring revealed an imrovement of cardiac conduction. The treadmill test was repeated and showed conduction improvement during effort, however the test was suspended due to the occurrence of ventricular couples and ventricular bigeminy during effort. For arrhythmic risk assessment, electrophysiological study (EPS) was performed and no arrhythmias were induced. We decided to defer ICD implantation. However, a loop–recorder for continuous arrhythmias monitoring was implanted. At three months, a new CMR was performed and was identical to the previous one, with no significant LGE reduction or increase detected.